2015
DOI: 10.1155/2015/916780
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines for TB: Lessons from the Past Translating into Future Potentials

Abstract: Development of vaccines for infectious diseases has come a long way with recent advancements in adjuvant developments and discovery of new antigens that are capable of eliciting strong immunological responses for sterile eradication of disease. Tuberculosis (TB) that kills nearly 2 million of the population every year is also one of the highlights of the recent developments. The availability or not of diagnostic methods for infection has implications for the control of the disease by the health systems but is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 92 publications
(82 reference statements)
0
4
0
1
Order By: Relevance
“…The majority of candidate vaccines were focused on improving CMI either by engineering the present BCG vaccine or using mycobacterial antigens that elicited Th1 responses as boosters after BCG priming. Interestingly, the vaccine strategies that use the whole cell (such as M. indicus pranii ) has reached phase III of clinical trials ( Weiner and Kaufmann, 2014 ; Tye et al, 2015 ). The success of this may be owing to a balanced stimulation of both CMI and AMI wings rather than trying to bias the same toward CMI.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of candidate vaccines were focused on improving CMI either by engineering the present BCG vaccine or using mycobacterial antigens that elicited Th1 responses as boosters after BCG priming. Interestingly, the vaccine strategies that use the whole cell (such as M. indicus pranii ) has reached phase III of clinical trials ( Weiner and Kaufmann, 2014 ; Tye et al, 2015 ). The success of this may be owing to a balanced stimulation of both CMI and AMI wings rather than trying to bias the same toward CMI.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in another study, 70% mutations were found in 306, 406 or 497 codons, 13% mutations outside the three regions between codons 296 and 426 and 15% mutations in the embC-embA intergenic region among the total 98% of mutations in the embCAB locus (Brossier et al, 2015 ). Recently, mutations in embB along with mutations in ubiA , encoding for a decaprenylphosphoryl-5-phosphoribose (DPPR) synthase associated with arabinogalactan synthesis pathway, were associated with high level of resistance to EMB (Tye et al, 2015 ).…”
Section: Molecular Targets Related Drug Resistance Mechanisms In Mdr-mentioning
confidence: 99%
“…По результатам исследований [28][29][30] установлено, что появление мутаций в гене ubiA, кодирующего декапренилфосфорил-5-фосфорибоз-синтазу (биосинтез арабиногалактана), приводит к невосприимчивости M. tuberculosis к схеме лечения, включающей в себя декстро-2,2'-этилендиимин-ди-1-бу та нол (этам бутол).…”
Section: молекулярные механизмы устойчивости к этамбутолуunclassified